Valuasi Ekonomi Ekosistem Mangrove di Kelurahan Kawal Kabupaten Bintan - khairunnisa; Abdillah, Yasir; Wahyudin, Wahyudin (MarIslands, 2024)
Kawal Village is one of the areas in Bintan Regency with a position bordering the sea. This area has an area of ??Ã‚Â± 1630 ha of mangrove forest and swamp forest. The people of Kawal Village use mangroves as a place to find fish, mangrove crabs, and shrimp. This study aims to calculate and determine the total economic value of the mangrove ecosystem in Kawal Village. Analysis of the data used is economic valuation in the form of direct use value and total economic value. The condition of the mangrove ecosystem based on the value of direct benefits and indirect benefits shows that the mangrove ecosystem in Kawal Village is very helpful for the community both from the economy and existence. The total economic value of the mangrove ecosystem in Kawal Village is Rp7.729.044.095/year.